2018
DOI: 10.4236/aim.2018.810053
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antimicrobial Susceptibility of <i>Yersinia enterocolitica</i> Found in Chitterlings, Raw Milk and Swine Fecal Samples

Abstract: Foodborne illness is an escalating concern upon public health. The prevalence of Yersinia enterocolitica was assessed in chitterlings, raw milk and swine fecal from North Carolina. Uncleaned thirty chitterling samples procured from a local grocery store, forty-five swine fecal samples, and forty unpasteurized cow milk samples supplied by the University farm were evaluated for the presence of Y. enterocolitica. Isolates identified as presumptive positive were characterized as colonies with a pink or deep-red ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…The colonial appearance (characteristic bull's eye appearance on CIN media) and the biochemical profile of Y. enterocolitica isolated was similar to those previously reported by Wanger (2007); Markey et al (2013) and FDA (2015) and Drake et al (2018). In addition, the biotyping tests for isolated Y. enterocolitica showed that, all of them were biotype 1A and biotype 1B only.…”
Section: Discussionsupporting
confidence: 87%
“…The colonial appearance (characteristic bull's eye appearance on CIN media) and the biochemical profile of Y. enterocolitica isolated was similar to those previously reported by Wanger (2007); Markey et al (2013) and FDA (2015) and Drake et al (2018). In addition, the biotyping tests for isolated Y. enterocolitica showed that, all of them were biotype 1A and biotype 1B only.…”
Section: Discussionsupporting
confidence: 87%
“…Then incubated at 37°C for 48 hours. Characteristic colonies appeared as bull's eyes ( Drake et al , 2018 ).…”
Section: Methodsmentioning
confidence: 99%